2021
DOI: 10.1111/trf.16496
|View full text |Cite
|
Sign up to set email alerts
|

Massive transfusions and severe hypocalcemia: An opportunity for monitoring and supplementation guidelines

Abstract: Background Massive transfusion protocols (MTPs) are associated with severe hypocalcemia, contributing to coagulopathy and mortality in severely injured patients. Severity of hypocalcemia following massive transfusion activation and appropriate treatment strategies remain undefined. Study design and methods This was a retrospective study of all MTP activations in adult trauma patients at a Level 1 trauma center between August 2016 and September 2017. Units of blood products transfused, ionized calcium levels, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 21 publications
2
14
0
Order By: Relevance
“…Giancarelli et al only looked at ionized calcium at one moment in time whereas we looked over a period to review a trajectory and assess for potential timing of intervention. Several recent studies have measured the incidence of hypocalcemia during massive transfusion and found similarly high incidences [7,[9][10][11].…”
Section: Previous Studies On Hypocalcemia From Massive Transfusionmentioning
confidence: 95%
See 1 more Smart Citation
“…Giancarelli et al only looked at ionized calcium at one moment in time whereas we looked over a period to review a trajectory and assess for potential timing of intervention. Several recent studies have measured the incidence of hypocalcemia during massive transfusion and found similarly high incidences [7,[9][10][11].…”
Section: Previous Studies On Hypocalcemia From Massive Transfusionmentioning
confidence: 95%
“…Clinical signs of hypocalcemia include heart failure, prolonged QT interval, sinus tachycardia, paresthesia, muscle spasms, cramps, tetany, circumoral numbness, and seizures [8]. Given the integral role that calcium plays in coagulation and hemodynamics, it is no surprise that several studies have shown a correlation between hypocalcemia and mortality [7,[9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…1,2 Decreased cardiac contractility occurs when ionized calcium levels drop below 0.8-0.9 mmol/L, 31 levels that have been demonstrated postinjury and are associated with increased mortality. 7,12,17,32 Administration of calcium chloride temporarily improves refractory shock by increasing cardiac contractility. 2,17 In states of decreased contractility, blood pressure is normally maintained by increasing afterload through vascular smooth muscle contraction.…”
Section: Physiological Derangements Associated With Hypocalcemiamentioning
confidence: 99%
“…39 This could explain the increased ventilation duration and decreased survival that has been reported in hypocalcemic patients. 6,13,17,32 Indeed, the profound shock state induced after a severe injury is a mix of hypovolemic, cardiogenic, and distributive shock which is intricately linked to hypocalcemia.…”
Section: Physiological Derangements Associated With Hypocalcemiamentioning
confidence: 99%
See 1 more Smart Citation